Kadar Muhammad Yusuf: The Concept of Learning The Quran From A Religious Figure From Riau - Salamah Salamah; Veni Sofia; Fauziah Rahmi; Alfazri Alfazri; Restu Maulana Ginanzar; Muh Irfan Ali (Al Hikmah: Journal of Education, 2026)
Islamic education plays a strategic role in shaping the personality of a person who is faithful, knowledgeable, and has noble character. However, the reality of contemporary education shows a tendency towards the dominance of a cognitive-instrumental approach that ignores the spiritual dimension and character formation. This condition demands a revitalization of the concept of learning that is holistic and oriented towards personality development. This study aims to examine in depth the concept of learning according to Kadar Muhammad Yusuf, a local religious figure in Riau, including the nature, principles, sources, methods, and objectives of learning, as well as its implications for the development of contemporary Islamic education. This study uses a qualitative approach with a library research method. Data were collected through documentation studies of relevant works and literature, then analyzed using content analysis techniques with source and theory triangulation to ensure data validity. The results show that Kadar Muhammad Yusuf's concept of learning is holistic, integrative, and transformative. The essence of learning is understood as an activity that builds cognition, skills, attitudes, spiritual awareness, and social piety. The principles of learning are based on monotheism, sincerity, and a clear goal orientation. Learning resources include the Qur'an, Sunnah, and the universe as an integrative epistemological basis. The learning method emphasizes a dialogical, reflective, and humanistic approach through al-hikmah (wisdom), mau'izah al-hasanah (experimental reasoning), mujadalah (religious reasoning), amtsal (practical practice), stories, and questioning. The ultimate goal of learning is directed at developing vertical and horizontal piety. These findings confirm that Kadar Muhammad Yusuf's learning concept is relevant in addressing the challenges of contemporary Islamic education, particularly in developing a learning model oriented toward the integration of knowledge, faith, and morals.